العلاقة بين القيمة المضافة للصناعات التحويليّة وتطور الصناعات التحويليّة في سورية - عكروش, محمد; حميدي, علي (Latakia University Journal - Economic and Legal Sciences Series, 2017)
يهدف هذا البحث إلى تسليط الضوء على مفهوم القيمة المضافة التحويليّة والاستراتيجيّة التنموية في سورية, بالإضافة إلى دراسة العلاقة بين بين القيمة المضافة للصناعات التحويليّة وتطور الصناعات التحويليّة في سورية خلال الفترة 2001-2010, وذلك باستخدام الانحدار البسيط, حيث كان من أهم النتائج التي تمّ التوصّل إليها:1. تبين وجود أثر لمعظم الصناعات التحويلية من حيث القيمة المضافة في تطور الصناعات التحويلية وكان أشدها تأثيرا هو صناعة الخشب.2. لا توجد علاقة ذات دلالة إحصائيّة بين القيمة المضافة للصناعات (الكيماويات) واجمالي ناتج الصناعات التحويليةوقد تم التوصل إلى التوصيات التالية:1. ضرورة إعطاء القيمة المضافة الأهمية اللازمة في الدراسات اللاحقة لما لها من مؤشر تنموي ودليل تطور قطاع على حساب القطاعات الاخرى2. التركيز على قطاعات الصناعات الكيماوية, والمعادن الاساسيّة, والتي أظهرت عدم دلالة في أثر قيمها المضافة في الناتج بالتالي ضعف المساهمة في التنميةThis research aims to shed light on the concept of value-added manufacturing and development strategy in Syria, in addition to the study of the relationship between the value-added manufacturing and the development of manufacturing industries in Syria during the period 2001-2010, using simple regression, where it was the most important results that have been reached to:• show a effect most of the manufacturing industries in terms of value added in manufacturing and development of the most influential is the wood industry• There were no statistically significant differences between the value-added industries relationship (chemicals) and total manufacturing outputIt has been reached following recommendations:• the need to give due importance to the value added in subsequent studies because of their developmental index and guide the development sector at the expense of other sectors• Focus on chemical industries, basic metals, which showed no significant differences in the impact of the added values in the resulting weakness thus contributing to the development